Analisis Nilai-Nilai Moral dalam Novel “Sisi Tergelap Surga” Karya Brian Khrisna dan Implikasinya pada Pembelajaran Bahasa Indonesia - Akbar, Akbar Julian; Samosir, Astuti; Rejeki, Suyekti Kinanthi (Jurnal Pendidikan Impola, 2025)
Literary works serve not only as entertainment but also as an effective medium for conveying moral messages to readers. Brian Khrisna's novel Sisi Tergelap Surga (The Darkest Side of Heaven) presents the story of characters struggling in the harshness of city life, with various inner conflicts and social issues that reflect the reality of lower-class society. This study aims to identify the moral values contained in the novel and explore their relationship to Indonesian language learning in schools. This study uses a descriptive qualitative method with content analysis techniques. Data were collected through intensive reading of the novel text, recording quotations containing moral values, and then grouping them into three types of relationships: humans with themselves, humans with others, and humans with God. The research instrument was a moral value classification table. Based on the analysis, several values were found, such as empathy, responsibility, honesty, justice, determination, and sacrifice. These values are displayed through the attitudes, dialogues of the characters, and the story's setting, which clearly depicts social inequality. This study concludes that this novel has great potential to be used as teaching material in literature learning in Indonesian language classes, especially in efforts to instill character values in accordance with the spirit of the Independent Curriculum. Keywords: moral values, novel, Indonesian language learning.